Factors that contribute to work stress among staff in Pejabat Tanah dan Galian negeri Selangor / Mohamad Yazid Yahya, Rudy Hartono Adeni and Zafirah Zainuddin - Yahya, Mohamad Yazid; Adeni, Rudy Hartono; Zainuddin, Zafirah (Arshad Ayub Graduate Business School, 2018)
This research presents a study on determining factors that contribute to work stress among staff in Pejabat Tanah dan Galian Negeri Selangor (PTGS). Based on the questionnaires and interviews carried out with the representatives in PTGS, it was found that there were few factors that contribute to work stress among PTGS staff during the ‘Data Cleaning Project’. The management of PTGS was concerned on what was causing the stress among employees. Therefore, this study is aimed to find factors which are significantly responsible for causing work stress during the exercise. This study was done using qualitative and quantitative methods which include interviews with the PTGS representatives and questionnaires which were distributed among the staff. The correlation test was used to determine whether there are a significant relationships between the independent variable and the dependent variable. Furthermore, Regression Analysis (Standard Multiple Regression) was used to examine which variables influenced the dependent variable the most. The study suggests that employees should take time to recharge in order to avoid any worsened consequences that may occur due to prolonged stress which may affect their performance and health. The results of the study also suggest that PTGS management should apply more effective communication methods to enhance feedback on bad working conditions from employees. Moreover, the study also suggests that the PTGS management should arrange or promote peer support training, which includes continuous learning and skill development to ensure that employees have the skill and knowledge to work efficiently. This training could build morale, sense of urgency, shared purpose and value among the peer support team. Besides that, it could detect erosion and burnout among colleagues that could trigger a red flag for any action or early prevention of deteriorating mental health among employees.